Fisheye omnidirectional stereo depth estimation assisted with edge-awareness - Junren Sun; Hao Xue; Shibo Guo; Xunqi Zheng (Frontiers in Physics)
The wide field of view of fisheye cameras introduces significant image distortion, making accurate depth estimation more challenging compared to pinhole camera models. This paper proposes a fisheye camera panoramic depth estimation network based on edge awareness, aimed at improving depth estimation accuracy for fisheye images. We design an Edge-Aware Module (EAM) that dynamically weights features extracted by a Residual Convolutional Neural Network (Residual CNN) using the extracted edge information. Subsequently, a spherical alignment method is used to map image features from different cameras to a unified spherical coordinate system. A cost volume is built for different depth hypotheses, which is then regularized using a 3D convolutional network. To address the issue of depth value discretization, we employ a hybrid classification and regression strategy: the classification branch predicts the probability distribution of depth categories, while the regression branch uses weighted linear interpolation to compute the final depth values based on these probabilities. Experimental results demonstrate that our method outperforms existing approaches in terms of depth estimation accuracy and object structure representation on the OmniThings, OmniHouse, and Urban Dataset (sunny). Therefore, our method provides a more accurate depth estimation solution for fisheye cameras, effectively handling the strong distortion inherent in fisheye images, with improved performance in both depth estimation and detail preservation.